(untitled) (Journal of Mathematical Study, 2023)
Let p, q be odd primes, and let d be an odd square-free integer such that (pq,d)=1. We show that slightly degenerate fusion categories of Frobenius-Perron dimensions 2p^2q^2d, 2p^2q^3d and 2p^3q^3d are group-theoretical.